Analysis of Antidiabetic Potential of Palmitic Acid Compounds Through In Silico Activation - Salsabila, Ardellya Elfidaa; Susanti, Nurlaili; Ulhaq, Zulvikar Syambani (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2022)
Diabetes Mellitus is a condition where the body's sugar level exceeds the blood's normal limit. Type 2 Diabetes Mellitus is the most common type of diabetes and is a chronic disease caused by insulin resistance and beta-cell dysfunction, resulting in decreased insulin sensitivity. The management of diabetes Mellitus is in the form of oral hypoglycemic drugs. Still, these drugs have side effects such as gastrointestinal disturbances, nausea, vomiting, hypoglycemia, macrovascular disorders, microvascular disorders, etc. So, it is necessary to seek alternative drugs to increase insulin sensitivity to lower blood sugar levels which are safer using herbal plants. One of the suspected plants that can be an alternative medicine to reduce excess blood sugar levels is the dandang gendis plant ( Clinacanthus nutans ). The dandang gendis plant ( Clinacanthus nutans ) contains palmitic acid, which can reduce excess blood sugar levels in the blood. This study aims to determine the potential of palmitic acid compounds from the Dandang gendis plant as an in silico AMPK protein activator. Methods: Qualitative descriptive method using molecular docking in silico method to determine the affinity and interaction with palmitic acid compounds in the dandang gendis plant in activating AMPK protein. Docking between palmitic acid and AMPK produces an energy value (∆Gbind) of -5.3 kcal/mol. docking of metformin resulted in the lowest energy value (∆Gbind) of 5.1 kcal/mol. The bond produced by palmitic acid docking has a fairly strong affinity for the AMPK protein of -5.3 kcal/mol. So palmitic acid, an ingredient in the dandang gendis plant (Clinacanthus nutans) has the potential as an antidiabetic.